2011
DOI: 10.5251/ajbms.2011.1.2.39.44
|View full text |Cite
|
Sign up to set email alerts
|

Identification of protein profiles of Escherichia coli, Staphylococcus aureus and their corresponding phages

Abstract: The present study was carried out for the assessment and detecting of the Escherichia coli and Staphylococcus aureus bacteriophages and their bacterial host's proteins includes visual inspection and comparison of their molecular weight mass. Systematic methods that use microorganisms (viruses and bacteria) to test samples from the local sewage water have been developed but require some change in the classical culturing of the organism to detect it easily by naked eye through the changes in selective media. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
4
3
0
Order By: Relevance
“…The results of our assessment of the purity of bacteriophages obtained by SDS-PAGE (Figure 2) were similar to those reported previously for other phage types [42,43]. It was interesting to note that the SDS-PAGE profiles of the ion-exchange-and cesium chloride-purified phages were very similar.…”
Section: Phage Purificationsupporting
confidence: 75%
“…The results of our assessment of the purity of bacteriophages obtained by SDS-PAGE (Figure 2) were similar to those reported previously for other phage types [42,43]. It was interesting to note that the SDS-PAGE profiles of the ion-exchange-and cesium chloride-purified phages were very similar.…”
Section: Phage Purificationsupporting
confidence: 75%
“…The similarity in molecular weights of their protein bands corroborates the study by Durrani et al (8) who also recorded similar molecular weights of protein bands of E. coli isolated from stool and urine samples. In a similar study, Chong et al [23] and Elshayeb et al [24] also recorded similar protein profile pattern of E. coli in their studies.…”
Section: Resultssupporting
confidence: 58%
“…Φ241 phage specific to E. coli O157:H7 had 13 protein bands and four of them were major proteins whose molecular weights were the range of 26–50 kDa (Lu and Breidt, 2015). Elshayeb et al. (2011) reported that E. coli bacteriophage had three major protein bands with molecular weights of 16, 35, and 47 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…(2018) reported that three bacteriophages had one major protein band (52 kDa). The molecular weights of the capsid proteins, which account for about 43.3% of the total phage proteins, are 34.3–47.7 kDa and the tail proteins constitute 12.7% of the total proteins and the molecular weights are between 22.5 and 27 kDa (Elshayeb et al., 2011; Zimmer et al., 2002).
Figure 4.SDS-PAGE gel images of E. coli O157:H7-specific bacteriophages. 1: vB_EcoM-P13; 2: vB_EcoM-P23; 3: vB_EcoM-P34; 4: vB_EcoS-P24; 5: vB_EcoM-P12; 6: marker (Bio-Rad unstained broad range protein standards).
…”
Section: Resultsmentioning
confidence: 99%